The Properties of Intuitionistic Anti Fuzzy Module t-norm and t-conorm - Wijaya, Ongky Denny; Alghofari, Abdul Rouf; Hidayat, Noor; Muslikh, Mohamad (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Zadeh have introduced fuzzy set in 1965 and Atanassov have introduced intuitionistic fuzzy set in 1986 in theirs paper. Now, many of researcher connecting intuitionistic fuzzy set with algebraic structure. We interested to combine some concepts over intuitionistic fuzzy set, module of a ring, t-norm, t-conorm, and intuitionistic anti fuzzy. In this paper, we discusses about intuitionistic anti fuzzy module t-norm and t-conorm (IAFMTC) and their properties with respect to module homomorphism, maps, pre-image, and anti-image from intuitionistic fuzzy sets. We have investigate all properties of IAFMTC.